THE INFLUENCE OF FINANCIAL LITERACY, REGRET AVERSION BIAS, AND OVERCONFIDENCE ON INVESTMENT DECISION - Tifany, Angela; Pamungkas, Ary Satria (Graduate Program of Universitas Tarumanagara, 2023)
Investment decision is a policy taken by investors as an alternative to achieve future profits. By comparing the average salary of formal employees in Jakarta with the cost of living in Jakarta, a question arises about how investors in Jakarta who work as worker make their investment decisions based on their investment capital. The purpose of this study is to examine the effect of Financial Literacy, Regret Aversion Bias, and Overconfidence on Investment Decision among workers in Jakarta. The sample of this study are the workers who work and live in Jakarta that make investment in the capital market. The number of samples in this study was 228 respondents that were obtained by purposive sampling method. This study used Structural Equation Modelling (SEM) for data analysis and using Likert scale as the measurement scale. The result of this study indicated that Financial Literacy, Regret Aversion Bias, and Overconfidence have a positive effect on Investment Decision.